Genotyping of Human Papilloma Virus Causing Skin Wart among Iraqi Patients - Mohammed Ghani Madlu; Wissam Saleh Abood (Indian Journal of Forensic Medicine & Toxicology, 2021)
The papillomaviruses are a large group of tiny, non-enveloped DNA viruses that in several differentanatomical locations can cause squamous epithelial tumor’s (warts and papilloma’s). There is a closeassociation between HPV and cervical uterine cancer . The genome is composed of 7200–8000 base pairsand is divided into three parts, early region (E) comprising of E1, E2, E4–E8 and reflecting 50 percent of theL1 and L2 genome, Genomic DNA from wart tissue samples were extracted by using gSYAN DNA mini kitextraction kit . The Real Time PCR primers for detection and genotyping of DNA Human papillomavirustype 1 and type3 and type6 based on L1 gene that designed in this study using NCBI-Genbank Sequencedatabase and primer 3 plus . The genetic study included analysis of a common DNA to HPV that was foundin 20 % of cases and DNA fragment specific to HPV type 1, 3 and 6 based on real time PCR. Type 1 HPVwas not approved to present in any sample in the study. Type 3 HPV was identified in a single case. HPV 6was identified in 8 cases, Therefore, type 6 HPV is the most common genotype, followed by type 3.